Strengthening Bank Regulation and Supervision : National Progress and Gaps - Dordevic, Ljubica (Departmental Papers; Departmental Paper, 2021)
The paper employs two complementary strategies. First, it is pursues textual analysis (text mining) of the assessment reports to identify successes and challenges the authorities are facing. Second, it analyzes the grades in the Basel Core Principles assessments, including their evolution and association with bank fragility.